Understanding patient characteristics and medication prescriptions in children with mental health and neurodevelopmental disorders referred to a sleep clinic—A quality improvement/quality assurance analysis - Ipsiroglu, Osman S.; Bhathella, Juhi; Boldut, Renee Paula; Elbe, Dean; Hill, Olivia; Keys, Elizabeth; McWilliams, Scout; Silvestri, Rosalia; Wensley, David F. (Frontiers in Psychiatry, 2022)
Introduction. Motivated by challenges faced in outpatient sleep services for mental health and neurodevelopmental disorders during the COVID-19 clinical shutdown, a pan-Canadian/international working group of clinicians and social scientists developed a concept how to capture challenging sleep and wake behaviours already at the referral stage in the community setting. Methods. In a quality improvement/quality assurance (QIQA) project, a visual logic model was the framework for identifying the multiple causes and possible interventions for sleep disturbances. Intake forms informed clinicians about situational experiences, goals/concerns, in addition to the questions from the Sleep Disturbances Scale for Children (SDSC), the ADHD Rating Scale-IV and medication history. Descriptive statistics was used to describe the sample. Results. 66% of the pilot study patients (n=41/51) scored in the SDSC red domains (highest scoring) with highest subscores for insomnia (falling asleep 73%; staying asleep: 51%) and daytime somnolence (27%). 90% of patients were taking at least one medication; 59% sleep initiation/sleep medications, 41% in combination with further non-stimulant medications, 9% with stimulants, 27% with antidepressants and 18% with antipsychotics. Polypharmacy was observed in 62% of all patients and in 73% of the ones medicated for sleep disturbances. Qualitative information supported individualization of assessments. Conclusion. Our intake process allowed a comprehensive understanding of patients’ sleep and wake profile already at the referral stage. The high prevalence of insomnia in patients, combined with polypharmacy, requires special attention in the triaging process already at the community level.